2022
DOI: 10.3390/nano12142433
|View full text |Cite
|
Sign up to set email alerts
|

Flame Retardant Nano-Structured Fillers from Huntite/Hydromagnesite Minerals

Abstract: In the current study, we propose a simple hydrothermal pathway to synthesize nano-structured Mg(OH)2 after application of thermal decomposition followed by hydration of commercial minerals based on hydromagnesite and huntite. The synthesis of nano-materials is performed without the use of any catalyst. The effect of decomposition temperature on the hydrothermal synthesis of Mg(OH)2 is extensively studied. It is shown that the morphology of resulting structures consists typically of particles ~200 nm in diamete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 25 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…The mineral huntite, H5, was kindly provided by the company Sibelco (Sibelco Hellas SA, Thessaloniki, Greece) and consisted of a huntite/hydromagnesite mixture, 88/12 wt./wt. %; the ratio was calculated by neglecting minor concentrations of other minerals, mostly dolomite [14,19,45]. Ultrapure water was obtained by means of an SG apparatus water purification unit.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The mineral huntite, H5, was kindly provided by the company Sibelco (Sibelco Hellas SA, Thessaloniki, Greece) and consisted of a huntite/hydromagnesite mixture, 88/12 wt./wt. %; the ratio was calculated by neglecting minor concentrations of other minerals, mostly dolomite [14,19,45]. Ultrapure water was obtained by means of an SG apparatus water purification unit.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, a higher percentage of H5 is incorporated into the polymer reducing the temperature of the cracking process and releasing a higher percentage of water vapor that dilutes the combustible gases, as well as the flammable acetic acid formed during the decomposition of PVAc [48,49]. Finally, a higher percentage of char is generated through the formation of mainly MgO but also CaO, resulting from the thermal decomposition of huntite, which protects the substrate (polymeric matrix) [45]. The addition of the copolymer P(SSH-co-SSBTPB60) as an additive kept the system's combustibility at low levels with an LOI value of 31%.…”
Section: Ii-e-h5 Ii-b-h5mentioning
confidence: 99%
See 2 more Smart Citations
“…The particle size analysis results indicated that the as-prepared products were in the mean size range of 274.5–289.7 nm. The multielement composition (carbon, oxygen, silicon, sulfur, calcium, and potassium) and high decomposition temperature of nano-sized fillers suggest their potential application in the field of flame retardants [ 68 , 69 ]. Besides the biomass raw materials, another important issue in consideration of critical environmental pollution is how to reuse the existing petroleum-based material [ 70 , 71 , 72 ].…”
Section: Ball Milling-assisted Fabrication Of Flame Retardantsmentioning
confidence: 99%